Fatigue and quality of life among professional ballroom dancers in brazil Fadiga e qualidade de vida em bailarinos profissionais de dança de salão no Brasil - Cardoso A.A. (2021)
© 2021, Associacao Brasileira de Pos - Graduacao em Saude Coletiva. All rights reserved.The scope of this study was to analyze the relationship between quality of life, fatigue and injuries among professional Brazilian ballroom dancers. A total of 320 professionals from the five regions of Brazil participated, and the data were collected through a self-administered online questionnaire concerning general information, WHOQOL-bref, Yoshitake Fatigue Questionnaire and Injury Identification in Dancers Questionnaire. For data analysis, descriptive statistics were used, followed by inferential analysis and the Multiple Linear Regression test. The results show that greater fatigue is associated with a negative quality of life, revealing that, for each additional increment in total fatigue, the quality of life is expected to decrease by 0.218 points in the physical domain; 0.226 points in the psychological domain; 0.420 points in the social domain; and 0.304 points in the environmental domain. In contrast, the incidence and intensity of injuries were not associated with quality of life. The conclusion drawn is that the context of professional ballroom dance can influence both the presence of fatigue and the quality of life. It is suggested that health professionals working with these dancers perform multifactorial interventions in order to reduce fatigue, attenuating its effects on quality of life.